Everyday bias : identifying and navigating unconscious judgments in our daily lives - Ross, Howard J. (Lanham, Maryland : Rowman & Littlefield, 2014)
If you are human, you are biased. From this fundamental truth, Howard Ross explores the biases we each carry within us. Most people do not see themselves as biased towards people of different races or different genders. And yet in virtually every area of modern life disparities remain. Even in corporate America, which has for the most part embraced the idea of diversity as a mainstream idea, patterns of disparity remain rampant. Why? Breakthroughs in the cognitive and neurosciences give some idea why our results seem inconsistent with our intentions. Bias is natural to the human mind, a survival mechanism that is fundamental to our identity. And overwhelmingly it is unconscious. Incorporating anecdotes from today's headlines alongside case studies from over 30 years as a nationally prominent diversity consultant, Ross help readers understand how unconscious bias impacts our day-to-day lives and particularly our daily work lives. And, he answers the question: Is there anything we can do about it? by providing examples of behaviors that the reader can engage in to disengage the impact of their own biases. With an added appendix that includes lessons for handling conflict and bias in the workplace, this book offers a resource for a broad audience, from individuals seeking to understand and confront their own biases to human resource professionals and business leaders determined to create more bias-conscious organizations in the belief that productivity, personal happiness, and social growth are possible if we first understand the widespread and powerful nature of the biases we don t realize we have.
Introduction: Blinded by the light of our bias -- If you are human, you are biased -- Thinking about thinking -- The many faces of bias -- Life, death and unconscious bias on a rainy night -- Who has the power? -- Like water for the fish: Networks of bias in everyday life -- Shifting to neutral: How we can learn to disengage from bias -- Incubators of consciousness: Creating more conscious organization -- Conclusion: A brave new world, a grand new journey.
Includes bibliographical references (pages 161-167) and index.
Keywords: Prejudices